2018
DOI: 10.1523/jneurosci.2080-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CRFR1-Dependent Regulation of a Ventral Tegmental Area to Prelimbic Cortex Projection Establishes Susceptibility to Stress-Induced Cocaine Seeking

Abstract: The ability of stress to trigger cocaine seeking in humans and rodents is variable and is determined by the amount and pattern of prior drug use. This study examined the role of a corticotropin releasing factor (CRF)-regulated dopaminergic projection from the ventral tegmental area (VTA) to the prelimbic cortex in shock-induced cocaine seeking and its recruitment under self-administration conditions that establish relapse vulnerability. Male rats with a history of daily long-access (LgA; 14 ϫ 6 h/d) but not sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Altogether, these findings suggest that CRF release into the VTA from neurons originating in the BNST activates CRFR1 receptors to excite VTA dopamine neurons that project to the prelimbic cortex, resulting in dopamine release, D1 receptor activation, and cocaine seeking. Consistent with this model, we have found that pharmacological disconnection of the VTA-prelimbic cortex pathway by administration of the CRF-R1 antagonist, antalarmin, into the VTA in one hemisphere, and administration of the D1 receptor antagonist SCH 23,390 into the prelimbic cortex of the contralateral hemisphere prevents shock-triggered cocaine seeking following self-administration in rats (Vranjkovic et al, 2018).…”
Section: Prelimbic Pfc Dopamine and D1 Receptorssupporting
confidence: 66%
See 2 more Smart Citations
“…Altogether, these findings suggest that CRF release into the VTA from neurons originating in the BNST activates CRFR1 receptors to excite VTA dopamine neurons that project to the prelimbic cortex, resulting in dopamine release, D1 receptor activation, and cocaine seeking. Consistent with this model, we have found that pharmacological disconnection of the VTA-prelimbic cortex pathway by administration of the CRF-R1 antagonist, antalarmin, into the VTA in one hemisphere, and administration of the D1 receptor antagonist SCH 23,390 into the prelimbic cortex of the contralateral hemisphere prevents shock-triggered cocaine seeking following self-administration in rats (Vranjkovic et al, 2018).…”
Section: Prelimbic Pfc Dopamine and D1 Receptorssupporting
confidence: 66%
“…As is the case with footshock stress, the ability of intra-VTA micro-infusions to reinstate drug seeking is only observed in rats with a history of long-access cocaine self-administration (Blacktop et al, 2011). We have found that this recruitment of CRF-dependent cocaine seeking is associated with increased CRF-R1 mRNA levels in the VTA and a heightened CRF-R1-dependent Fos response in the prelimbic cortex (Vranjkovic et al, 2018). Based on these observations, we hypothesize that excessive cocaine use produces persistent increases in CRF-R1 receptors on VTA dopamine neurons that project to the prelimbic cortex, thereby promoting stress-induced drug seeking.…”
Section: History Of Drug Usementioning
confidence: 68%
See 1 more Smart Citation
“…Indeed, basal CRF levels in the VTA are elevated during drug withdrawal following cocaine self-administration, 8 which could potentially occlude the behavioral effect of exogenously applied CRF and/or elicit changes in CRF receptor expression within the VTA. Prior drug experience increases CRF receptor levels within the VTA 15,38,39 and alters the electrophysiological effects of CRF on VTA dopamine neurons. 14,16,17,37 As such, the cocaine-mediated loss in the capacity for CRF to regulate motivation could be mediated by (a) CRF losing the ability to inhibit dopamine transmission or (b) CRF engaging a local excitatory circuit to counteract its inhibitory influence over dopamine neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to abused substances elicits an array of intrinsic and synaptic changes within the VTA [32]. Prior drug experience increases CRF receptor levels within the VTA [9,33,34], and alters the electrophysiological effects of CRF on VTA dopamine neurons [8,10,11,31]. As such, the cocaine-mediated loss in the capacity for CRF to regulate motivation could be mediated by a drug-induced alteration in which CRF engages a local circuit to reverse its inhibitory influence on reward-evoked dopamine release.…”
Section: Discussionmentioning
confidence: 99%